Islamic Religiousity, Conspicuous Consumption, and PayLater Usage Intention in Young Muslim Consumers - Sulhaini Sulhaini; Laila Wardani; Sulaimiah Sulaimiah (Universitas Prasetiya Mulya, 2026)
The aim of the study is to investigate PayLater usage intentions among young Muslim consumers from Lombok Island, Indonesia. Muslim consumer behavior related to fintech usage has not been widely studied. Gender differences in Islamic religious commitment appear to have been overlooked in previous studies. Data were collected through questionnaires distributed to university students aged 17–25. The sample size was 316 students from various regencies on Lombok Island. Data analysis was conducted using AMOS 23. Results indicate that for all groups, Islamic religious commitment significantly attenuates the tendency to show off (males; β=0.808 p<0.001 and females; β=0.388 p<0.01). This study contributes by providing evidence that Muslim consumers’ tendency to show off drives their intention to take on debt. Gender differences are also demonstrated: the effect of Islamic religious commitment on the tendency to show off being significantly stronger for male consumers than for female consumers. However, this religious commitment does not have a direct negative impact on male consumers’ intention to take on debt; rather, it indirectly reduces this intention by attenuating the tendency to show off.